Effect of rumen escape amino acids and multiple TBA implants on feedlot performance of lightweight Holstein steer calves - Healy, B.J.; Brandt, Robert T., Jr.; Titgemeyer, Evan C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two hundred forty Holstein steers (343 lb) were stratified by weight and allotted to one of eight treatment combinations in a 2 × 4 factorial arrangement. Main effects were implant (Synovex-S (S) or Synovex-S + Finaplix-S (SF) on day 0, 87, 168, and 238 and level of rumen escape amino acids (Smartamine-ML (SML) at 0, 5, 10, or 15 grams/head/day). These levels of SML supplied 0, 2.75, 5.5, and 8.25 g/day of Llysine and 0, .75, 1.5, and 2.25 g/day of DL-methionine. Steers implanted with SF gained 4% faster, had a 4% improvement in feed:gain, a lower dressing percentage, 12% less backfat, 3.4% more rib-eye area, a lower yield grade, less marbling, and fewer Choice grades (P<.05) compared to S-implanted steers. Overall feed intake and carcass weights were similar between S- and SF-implanted steers. Use of SML resulted in a linear decline in hot carcass weight (P<.10) and KPH (P<.05), with other carcass traits unaffected. Increasing the level of SML tended to increase feed intake (P<.15), and quadratically degraded feed:gain (P<.10). Repeated implants of SF did not improve carcass worth and the use of rumen escape amino acids did not improve performance, suggesting that the basal diet was not first-limiting in lysine and(or) methionine.
Keywords: Beef; Estradiol; Trenbolone acetate; Rumen escape amino acids; Holstein; Steers